2019
DOI: 10.1186/s41938-019-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the entomopathogenic fungi as a non-traditional control of the rice leaf roller, Cnaphalocrocis medinalis (Guenee) (Lepidoptera: Pyralidae) under controlled conditions

Abstract: The rice leaf roller or leaf folder, Cnaphalocrocis medinalis (Guenee) (Lepidoptera: Pyralidae), is a serious pest of rice crop in Pakistan. The present study was carried out to evaluate the virulence of the entomopathogenic fungi (EPF) Beauveria bassiana, Verticillium lecanii, and Metarhizium anisopliae against the third instar of C. medinalis larvae. Larvae were exposed to fungi under controlled conditions at the available commercial concentration (1 × 10 8 conidia ml −1 ). The results showed 73.33, 57.78, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Batta (2004) found that the conidial viability of fungus decreased with time, but its insecticidal efficacy was not badly affected. This trend has also been reported in case of some greenhouse and field trials and pests such as the rice leaf roller, C. medinalis (Rizwan et al 2019), and the whitefly Bemisia tabaci (Gennadius) (Batta 2003), respectively. Fungal pathogens are more advantageous in bio-control cases as these could recycle in cadavers producing conidiospores that are reintroduced into the eco-system (Thomas et al 1997 andStathers 2002).…”
Section: Mycosis and Progeny Productionsupporting
confidence: 71%
See 1 more Smart Citation
“…Batta (2004) found that the conidial viability of fungus decreased with time, but its insecticidal efficacy was not badly affected. This trend has also been reported in case of some greenhouse and field trials and pests such as the rice leaf roller, C. medinalis (Rizwan et al 2019), and the whitefly Bemisia tabaci (Gennadius) (Batta 2003), respectively. Fungal pathogens are more advantageous in bio-control cases as these could recycle in cadavers producing conidiospores that are reintroduced into the eco-system (Thomas et al 1997 andStathers 2002).…”
Section: Mycosis and Progeny Productionsupporting
confidence: 71%
“…The strain of B. bassiana isolate used in this study was obtained from dead cadavers of rice leaf folder, Cnaphalocrocis medinalis (Guenée) (Rizwan et al 2019). The fungus was then sub-cultured on Potato Dextrose Agar (PDA) plates for bulk generation of the fungal conidia.…”
Section: Fungal Formulationsmentioning
confidence: 99%
“…Considerable advancements are reported in the field of insect pathology and the role of entomopathogenic microorganisms is widely investigated for effective pest control under controlled and open field conditions 14 . Currently, biopesticides are being used for insect pest management due to less hazardous impact on the environment, beneficial fauna, and ultimately human health 21 , 22 . Entomopathogenic fungi (EPFs) have been used for the management of insect pests ranging from stored grain pest management 23 , laboratory testing 22 , greenhouse assay 21 , and field trials 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, biopesticides are being used for insect pest management due to less hazardous impact on the environment, beneficial fauna, and ultimately human health 21 , 22 . Entomopathogenic fungi (EPFs) have been used for the management of insect pests ranging from stored grain pest management 23 , laboratory testing 22 , greenhouse assay 21 , and field trials 24 . However, studies regarding the impact of these biopesticides including EPFs on the biological control agents naturally present in the field are still a researchable topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation